Hydraulic Tensioning Of A Birmingham Roof Truss - C. W. Bollier (International Conference on Ground Control in Mining, 1982)
In recent years, Peabody Coal Company has enjoyed a great amount of success using roof trussing as a secondary support system. Since 1975, over 180,000 trusses have been installed in 12 different Peabody mines with varying geological conditions. Projections from Peabody, and throughout the mining industry, indicate a continuous growth in the trussing principle for roof control. Peabody's primary supplier has sold over 1,000,000 trusses to 50 different mines throughout the country. (1) Roof trusses provide an improved means of controlling difficult roof conditions which, in turn, improves worker safety and mine production. Since the original development of the truss, (2) the only major modification to the trussing procedure has been the addition of the resin point anchor system in the mid-70's. The resin point anchor was the catalyst needed to provide a reliable anchor and create acceptance of the roof truss by both management and labor. Peabody began using trusses in their mines in 1975. For the first few years, most of the truss effort was geared toward determining proper anchorage, spacing, and gathering historical data. In recent years, Peabody's activities have centered on the development of improving trussing procedures. Through monitoring and trussing activities, a number of areas of improvement have been found.